2012
DOI: 10.1007/s10865-012-9420-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal familism predicts weight management adherence in Mexican–American women

Abstract: Adherence to behavioral weight management programs is often limited, especially among ethnic minority populations. The current study examined whether attitudinal familism, or attention to the needs of family above those of the self, predicted poorer adherence to a behavioral weight management program in Mexican-American women. One-hundred overweight or obese Mexican-American women from the southwestern United States were enrolled in a group-based weight loss treatment. Zero-order correlations indicated that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…On the other hand, family cohesion may hinder healthy behaviors, for instance, through individuals prioritizing other family members' needs over their own well-being (Perez & Cruess, 2014). One study found that adherence to a weight management plan that included diet and exercise was lower among women who expressed greater familism, including cohesion (Austin et al, 2013). Other studies have found no relationship of family cohesion to health when other aspects of family relationships are controlled (Bostean, 2010).…”
Section: Family Cohesionmentioning
confidence: 99%
“…On the other hand, family cohesion may hinder healthy behaviors, for instance, through individuals prioritizing other family members' needs over their own well-being (Perez & Cruess, 2014). One study found that adherence to a weight management plan that included diet and exercise was lower among women who expressed greater familism, including cohesion (Austin et al, 2013). Other studies have found no relationship of family cohesion to health when other aspects of family relationships are controlled (Bostean, 2010).…”
Section: Family Cohesionmentioning
confidence: 99%
“…Cultural values, such as familismo (e.g., importance of family), have been shown by researchers to positively mediate health outcomes, participation in health services, and treatment adherence, highlighting the importance of cultural, not just linguistic, competence in health care delivery (Austin, Smith, Gianini, & Campos-Melady, 2013;Chong, 2002).…”
mentioning
confidence: 99%
“…Although familism is a cultural strength, high levels have been shown to interfere with successful weight loss treatment for Mexican American women (Austin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The matter of women not wishing to disrupt their families' lives and habits with their own weight loss efforts has arisen in other qualitative work with Mexican American women (Lindberg and Stevens, 2011;Shea et al, 2012). Additionally, previous studies have found that missed sessions are common in weight loss treatment with Latino individuals (Austin et al, 2013;Corsino et al, 2012). Clinicians should:…”
Section: Recommendationsmentioning
confidence: 99%